1975
DOI: 10.1038/257751a0
|View full text |Cite
|
Sign up to set email alerts
|

X-ray analysis of glucagon and its relationship to receptor binding

Abstract: X-ray analysis of the pancreatic hormone glucagon shows that in crystals the polypeptide adopts a mainly helical conformation, which is stabilised by hydrophobic interactions between molecules related by threefold symmetry. A model is presented in which the glucagon molecule exists in dilute solutions as an equilibrium population of conformers with little retention of conformers with little retention of structure, and in which the helical conformation is stablised by hydrophobic interactions either as an oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
174
2
2

Year Published

1977
1977
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(184 citation statements)
references
References 28 publications
6
174
2
2
Order By: Relevance
“…X-ray results show the participation of tryptophan-25, tyrosine-10 and -13, phenylalanine-6 and -22, and leucine-26 in interchain interactions (3). It has become clear since the original description by Kendrew (23) of the nonpolar interactions in myoglobin and the thermodynamic analyses by Kauzmann (24) and Scheraga (25) that hydrophobic interactions could account for most of the favorable free energy change involved in protein folding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray results show the participation of tryptophan-25, tyrosine-10 and -13, phenylalanine-6 and -22, and leucine-26 in interchain interactions (3). It has become clear since the original description by Kendrew (23) of the nonpolar interactions in myoglobin and the thermodynamic analyses by Kauzmann (24) and Scheraga (25) that hydrophobic interactions could account for most of the favorable free energy change involved in protein folding.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Gratzer et al (20) found, by crosslinking experiments with dimethyl suberimidate, that the associated species is a trimer; no dimers or hexamers were found. Moreover, xray studies show that glucagon is a timer in its crystalline state (3). A second assumption used for the analysis of the experimental data was that the ellipticities of the monomer and trimer are independent of temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially interesting is the comparison of the structures adopted by glucagon in single crystals (Sasaki et al 1975) and of MB-glucagon in a lipid-water interphase. The individual molecules of the trimer in the X-ray single crystal structure are mainly a-helical with hydrophobic contacts between the monomers.…”
Section: Micelle-bound Glucagonmentioning
confidence: 99%
“…The existence of unstructured proteins in a functional context has been recognized for many years. As early as the 1970s, the peptide hormone glucagon was recognized to be much more flexible than its counterpart insulin (1,2), and there are many other examples of partial or complete lack of stable three-dimensional structure among common hormones, such as oxytocin and somatostatin. An early puzzling observation that chromogranin stored in the chromaffin granules of the adrenal medulla is in an unstructured form in the functional, intact cells (3) can now be rationalized and compared with many other observations of stored proteins that are apparently 'random coil'.…”
mentioning
confidence: 99%